Spatial and temporal trends in exhumation of the Eastern Himalaya and syntaxis as determined from a multitechnique detrital thermochronological study of the Bengal Fan - Chew, David (My University, 2019)
The Bengal Fan provides a Neogene record of Eastern and Central Himalaya exhumation. We provide the first detrital thermochronological study (apatite and rutile U-Pb, mica Ar-Ar, zircon fission track) of sediment samples collected during International Ocean Discovery Program (IODP) Expedition 354 to the mid–Bengal Fan. Our data from rutile and zircon fission-track thermochronometry show a shift in lag times over the interval 5.59–3.47 Ma. The oldest sample with a lag time of <1 m.y. has a depositional age between 3.76 and 3.47 Ma, and these short lag times continue to be recorded upward in the core to the youngest sediments analyzed, deposited at <1 Ma. We interpret the earliest record of short lag times to represent the onset of extremely rapid exhumation of the Eastern Himalayan syntaxial massif, defined as the syntaxial region north of the Nam La Thrust. Below the interval characterized by short lag times, the youngest sample analyzed with long lag times (>6 m.y.) has a depositional age of 5.59–4.50 Ma, and the zircon and rutile populations then show a static peak until >12 Ma. This interval, from 5.59–4.50 Ma to >12 Ma, is most easily interpreted as recording passive erosion of the Greater Himalaya. However, single grains with lag times of <4 m.y., but with high analytical uncertainty, are recorded over this interval. For sediments older than 10 Ma, these grains were derived from the Greater Himalaya, which was exhuming rapidly until ca. 14 Ma. In sediments younger than 10 Ma, these grains could represent slower, yet still rapid, exhumation of the syntaxial antiform to the south of the massif. Lag times <1 m.y. are again recorded from 14.5 Ma to the base of the studied section at 17 Ma, reflecting a period of Greater Himalayan rapid exhumation. Mica 40Ar/39Ar and apatite U-Pb data are not sensitive to syntaxial exhumation: We ascribe this to the paucity of white mica in syntaxial lithologies, and to high levels of common Pb, resulting in U-Pb ages associated with unacceptably high uncertainties, respectively.
PUBLISHED
cited By 1
Keywords: Bengal Fan; Eastern and Central Himalaya exhumation